Variazione poetica, metamorfosi, ibridazione linguistica: scritture del corpo e identità in trasformazione nell'opera di Tawada Yōko - Francesco Eugenio Barbieri (Between, 2014)
A recurring theme in the work of Japanese writer Tawada Yōko is metamorphosis, intended first and foremost as body transformation, as the introduction in the story of an element of magic, and used to question the monolithic notion of identity in the global dimension of migrant citizenship. On the other hand linguistic metamorphosis - i.e. morphological, grammatical and syntactical hybridization between Japanese and German language - is another strategy frequently used by the writer to improve her textual expressive potential. This paper aims at presenting a brief analysis of the use of metamorphosis, both in its narrative and linguistic dimension, with reference to Tawada Yōko's Das Bad (1989), Opium für Ovid (2000) and Abenteuer der Deutschen Grammatik (2010).